Prove the following 1.A-(B ∩ C)=(A-B)U(A-C) 2.P(A) ∩ P(B)=P(A ∩ B)

Prove the following 
1.A-(B∩ C)=(A-B)U(A-C)
2.P(A)∩ P(B)=P(A∩ B)


1 Answers

Riddhish Bhalodia
askIITians Faculty 434 Points
6 years ago
1st can be solved by venn diagrams as shown in the figure
2ndis just common sense
LHS says = probability of being in A and probability of being in B
= probability of being in A and B = RHS
512-231_Photo on 08-05-16 at 1.31 PM.jpg

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy


Get your questions answered by the expert for free